Sharing medical data using a blockchain‐based secure EHR system for New Zealand. Issue 1 (2nd March 2022) - Huang, Jack; Qi, Yuan Wei; Asghar, Muhammad Rizwan; Meads, Andrew; Tu, Yu‐Cheng
Abstract: In New Zealand, the demand for healthcare services has grown gradually in the last decade, and it is likely to increase further. This had led to issues such as increasing treatment costs and processing time for the patients. To address the growing pressure in the healthcare sector, and its fragmented IT landscape that compounds the problems further, the New Zealand Ministry of Health aims to establish a shared Electronic Health Record (EHR) system that integrates all the major healthcare organisations such as hospitals, medical centres, and specialists. Due to its characteristics, blockchain technology could be a potential platform for building such large‐scale health systems. Here, MedBloc, a blockchain‐based secure EHR system that enables patients and healthcare providers to access and share health records while providing usability, security, and privacy is presented. MedBloc captures a longitudinal view of the patients' health story and empowers the patients to regulate their own data by allowing them to give or withdraw consent for healthcare providers to access their records. To preserve the patients' privacy and protect their health data, MedBloc uses an encryption scheme to secure records and smart contracts to enforce access control to prevent unauthorised access.